Calculation of Rational Rotational Speed of Cutting Discs during Their Ultrasonic Charging - M. G. Kiselev; D. A. Stepanenko (Наука и техника)
The paper contains an estimation of rational rotational speeds of cutting discs during their ultrasonic charging. It has been shown that in the case of ultrasound application it is necessary to reduce rotational speed of a disc in comparison with a conventional charging in order to provide its uniformity.